2017
DOI: 10.4314/njbas.v24i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Resource Appraisals of Bodinga and Environs, Sokoto Basin North Western Nigeria

Abstract: ABSTRACT:The groundwater resources of semi-arid region of Bodinga town and its environs within the Sokoto basin of Northwestern Nigeria have been evaluated. Data obtained at site during pumping test sessions which lasted for a period of between 8-12 hours for a total of 67 boreholes in the area of study were used alongside Information gathered from the careful analysis of lithological logs of the drilled Boreholes. The Hydraulic conductivity for the Kalambaina, Wurno, and Taloka formations are 22.00x10 m/s , 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Wamakko is characterized by the Sokoto Plains, a lowland topography, with an average height of about 300 meters above sea level. In a few places, the lowland is interrupted by isolated hills and escarpments such as those around Kalambaina [57,58] . Recent alluvial deposits along the river valley during the Quaternary era were observed by [55] .…”
Section: Relief and Geologymentioning
confidence: 99%
“…Wamakko is characterized by the Sokoto Plains, a lowland topography, with an average height of about 300 meters above sea level. In a few places, the lowland is interrupted by isolated hills and escarpments such as those around Kalambaina [57,58] . Recent alluvial deposits along the river valley during the Quaternary era were observed by [55] .…”
Section: Relief and Geologymentioning
confidence: 99%
“…There are series of interconnecting river systems with tributaries and distributaries within the basin. At the basin eastern source, it is joined by Konni River, the basin depicts traces of seasonality, and as it flows towards the western direction it becomes perennial owing to inputs from sub-surface flows from the vast Iullemeden geologic basin [27].…”
Section: Study Areamentioning
confidence: 99%
“…Literature on the application of these measures within the semi-arid ecosystem of West Africa remains a rarity. Existing measures are often based on non-spatial hydrological assessments such as [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…İn the north, including the Sokoto-Rima basin, optimal functioning of freshwater ecosystem service complexes remains seasonal hence the heavy reliance on dams and irrigation projects to supply urban and agrarian purposes. However, researches on water yield have often concentrated on annual water yield [8][9][10][12][13], while a few, such as [6][7], considered the import of seasonal water yield. These studies have shown that seasonal water yield is sufficient to capture the value of seasonal differences in water resource management, particularly for irrigation management, water requirements for crops, and urban water supplies in arid zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation